Protective effect of berberine against LPS-induced injury in the intestine: a review - Izadparast, Faezeh; Riahi-Zajani, Bamdad; Yarmohammadi, Fatemeh; Hayes, A. Wallace; Karimi, Gholamreza (Cell cycle (Georgetown, Tex.), 2022)
Sepsis is a systemic inflammatory condition caused by an unbalanced immunological response to infection, which affects numerous organs, including the intestines. Lipopolysaccharide (LPS; also known as endotoxin), a substance found in Gram-negative bacteria, plays a major role in sepsis and is mostly responsible for the disease's morbidity and mortality. Berberine is an isoquinoline alkaloid found in a variety of plant species that has anti-inflammatory properties. For many years, berberine has been used to treat intestinal inflammation and infection. Berberine has been reported to reduce LPS-induced intestinal damage. The potential pathways through which berberine protects against LPS-induced intestinal damage by inhibiting NF-κB, suppressing MAPK, modulating ApoM/S1P pathway, inhibiting COX-2, modulating Wnt/Beta-Catenin signaling pathway, and/or increasing ZIP14 expression are reviewed. Abbreviations: LPS, lipopolysaccharide; TLR, Toll-like receptor; MD-2, myeloid differentiation factor 2; CD14, cluster of differentiation 14; LBP, lipopolysaccharide-binding protein; MYD88, myeloid differentiation primary response 88; NF-κB, nuclear factor kappa light-chain enhancer of activated B cells; MAPK, mitogen-activated protein kinase; IL, interleukin; TNFα, tumor necrosis factor-alpha; Caco-2, cyanocobalamin uptake by human colon adenocarcinoma cell line; MLCK, myosin light-chain kinase; TJ, tight junction; IκBα, nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha; IBS, irritable bowel syndrome; ERK, extracellular signal-regulated kinase; JNK, c-Jun N-terminal kinase (JNK; GVB, gut-vascular barrier; ApoM, apolipoprotein M; S1P, sphingosine-1-phosphate; VE-cadherin, vascular endothelial cadherin; AJ, adherens junction; PV1, plasmalemma vesicle-associated protein-1; HDL, high-density lipoprotein; Wnt, wingless-related integration site; Fzd, 7-span transmembrane protein Frizzled; LRP, low-density lipoprotein receptor-related protein; TEER, transendothelial/transepithelial electrical resistance; COX-2, cyclooxygenase-2; iNOS, inducible nitric oxide synthase; IGF, insulin-like growth factor; IGFBP, insulin-like growth factor-binding protein; ZIP, Zrt-Irt-like protein; PPAR, peroxisome proliferator-activated receptors; p-PPAR, phosphorylated-peroxisome proliferator-activated receptors; ATF, activating transcription factors; SOD, superoxide dismutase; GSH-Px, glutathione peroxidase; SARA, subacute ruminal acidosis; IPEC-J2, porcine intestinal epithelial cells; ALI, acute lung injury; ARDS, acute respiratory distress syndrome